Demographic and attitudinal variables associated with consumers' intention to purchase green produced foods in Malaysia. - Rezai, Golnaz; Mohamed , ZainalAbidin; Shamsudin, Mad Nasir; Phuah, Kit Teng (2011)
The green concept and green foods are developing and are still at their infancy stage in Malaysia. Therefore, there is a need to examine Malaysian consumers’ attitude, perception and intention towards green food consumption. Thus, the objective of this study is to determine the extent to which selected socio-economic/demographic characteristics and attitudes influence the consumers’ intention to purchase green foods in Malaysia especially since there are emerging global issues concerned with the environment, food safety and animal welfare. A survey was conducted in Peninsular Malaysia where 1,355 respondents were interviewed using structured questionnaires to gather important information on their perception and intention to purchase green food in Malaysia. A binary logistic model was used to obtain the coefficients applied to the calculations of the marginal effects and probabilities. The results indicate that educational level, income and other factors such as food safety and environmental friendliness significantly influence Malaysian consumers’ green foods purchasing intention.